Impact of moderative ligand hydrolysis on morphology evolution and the morphology-dependent breathing effect performance of MIL-53(Al). Issue 15 (5th March 2018) - Liu, Dandan; Yan, Liting; Li, Liangjun; Gu, Xin; Dai, Pengcheng; Yang, Lingzhi; Liu, Yunqi; Liu, Chenguang; Zhao, Guoming; Zhao, Xuebo
Abstract : The deferred release of a ligand could modulate the morphology of MIL-53(Al), and different morphologies affect the breathing effect process. Abstract : In this paper, a facile route is reported for the synthesis of MIL-53(Al) particles with different sizes and morphologies via the addition of various ratios of an esterified ligand to realize the deferred release of the ligand. Detailed proof indicates that the hydrolysis and deferred release of the ligand play a crucial role in modulating the morphology and size of the obtained MIL-53 nanoparticles without disrupting the original structure and framework of MIL-53. A possible mechanism for the growth of MIL-53 crystals with different exposed facets is proposed based on the structure of MIL-53 and BFDH (Bravais, Friedel, Donnay and Harker) theory. In addition, the influence of the crystal morphologies or exposed surfaces on the breathing effect and gas adsorption performance was evaluated using N2 and CO2 adsorption, and the as-prepared MIL-53 particles showed different adsorption isotherms and adsorption behavior under the same conditions. The MIL-53 particles synthesized using an appropriate amount of an esterified ligand could present an enhanced surface area when compared to that of bulk MIL-53, and the breathing effect during CO2 adsorption was moderate, while excessive amounts of the esterified ligand resulted in a decrease in the porosity and the formation of boehmite. Based on the experiment, the discrepancy in the breathing effect is mainly attributed to the stability of the narrow pore form with different exposed facets, but not the decreased particle size.